Exploring family based immigrant youth substance use prevention programmes: a scoping review protocol. Issue 5 (26th May 2021) - Li, Yiyan; Maina, Geoffrey; Pandey, Mamata; Amoyaw, Jonathan; Fang, Yiting
Abstract : Introduction: Canada has one of the highest rates of problematic opiate and alcohol use in the world. Globally, Canada was the second country that legalized marijuana for non-medical use. As Canada is an immigrant-receiving country, newcomers and immigrants contend with a substance use landscape that was likely absent in their countries of origin. Although immigrants have lower rates of substance use than the host population, the risk of substance use, especially among youth, increases with acculturation and peer pressure. While parents are best placed to mitigate the risks for substance use among their youth, immigrant parents often do not have the knowledge and skills to do so. Therefore, culturally adaptable family based interventions need be explored to build immigrant parents' capacities to mitigate substance use risks. Aim and purpose: The aim of this scoping review is to explore family based substance use prevention interventions for immigrant youth, which will be guided by two questions: What is known about family based interventions for preventing immigrant adolescents' substance use? What are the features and study results of these intervention protocols? Methods and analysis: We will apply Arksey and O'Malley's procedure for reporting scoping review and report study findings based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for scoping reviews. Discussion: We hope that the knowledge translation emanating from this review will increase immigrant parents' knowledge of substance use and enable them to effectively intervene to prevent substance use among their youth. We also hope that this work can inform policy development on best practices for substance use prevention and for the creation of culturally sensitive programmes and services for immigrant youth.